(untitled) (Academic Journal of Internal Affairs, 2019)
Spring 2012 was basically transformed the legal regulation of infringement. From that time – breaking a tradition of 130 years – exclusively a law can prescribe what is to consider as an infringement, government and local governments have lost this opportunity. Simultaneously local government were entitled to regulate violating basic regulations of so-called communal cohabitation by own ordinances and to specify substantive sanction against perpetrators. Non-government organisations, the ombudsman and the Kuria (the highest court) immediately indicated that self-governments had gained an unlimited power for autocratic interference in citizens’ life on their territory by state coercive even without real violation of the community’s interests. The author makes proposals for legislation, application of law and organisation, feasible basically within a short period, to release the situation and offend legal certainty.